Immunological Control of Viral Infections in Bats and the Emergence of Viruses Highly Pathogenic to Humans - Schountz, Tony; Baker, Michelle L.; Butler, John; Munster, Vincent (Frontiers in Immunology, 2017)
Bats are reservoir hosts of many important viruses that cause substantial disease in humans, including coronaviruses, filoviruses, lyssaviruses and henipaviruses. The viruses do not appear to cause disease in the reservoir bats, thus an explanation for the dichotomous outcomes of infections of humans and bat reservoirs remains to be determined. Bats appear to have a few unusual features that may account for these differences, including evidence of constitutive interferon (IFN) activation and greater combinatorial diversity in immunoglobulin genes that do not undergo substantial affinity maturation. We propose these features may, in part, account for why bats can host these viruses without disease, and how they may contribute to the highly pathogenic nature of bat-borne viruses after spillover into humans. Because of the constitutive IFN activity, bat-borne viruses may be shed at low levels from bat cells. With large naïve antibody repertoires, bats may control the limited virus replication without the need for rapid affinity maturation, and this may explain why bats typically have low antibody titers to viruses. However, because bat viruses have evolved in high IFN environments, they have enhanced countermeasures against the IFN response. Thus, upon infection of human cells, where the IFN response is not constitutive, the viruses overwhelm the IFN response, leading to abundant virus replication and pathology.